Creating E-commerce for MSMES in Panjunan Village: Steps towards a Smart Village - Rahmawati, Dyah Putri; Amri, Arni Muarifah; Rahmawati, Dewi; Safitri, Pima Hani (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2024)
Micro, small, and medium enterprises (MSMEs) are crucial sectors that support economic growth in Indonesia. In the massive development of the digital economy, there has been a shift from offline to online transactions. MSME actors are now required to adopt technology to follow consumer shopping trends. One way to do this is by implementing e-commerce. The development of MSMEs through e-commerce is a smart step to increase visibility and market access. By leveraging e-commerce platforms, MSMEs can reach a wider audience, boost sales, and expand their business footprint without geographical limitations. In addition to digitalization, MSMEs need guidance in online sales, inventory management, digital marketing, and financial management. This guidance helps MSMEs maximize their potential in e-commerce. Desa Panjunan in Duduksampeyan District, Gresik Regency, is one village with MSME potential that needs to be developed through e-commerce. This community service activity will include creating an MSME e-commerce website for the village as a step towards becoming a Smart Village. The developed e-commerce has been tailored to the characteristics and needs of MSME actors in Desa Panjunan. This e-commerce initiative in Desa Panjunan can open up broader market access for local products, improve competitiveness, product quality, and MSME business management, as well as increase the income and welfare of the local community.